Analisis Makroekonomi Terapan: Kebijakan Finansial dan Transformasi Struktural Sulawesi Selatan: Applied Macroeconomic Analysis: Financial Policy and Structural Transformation of South Sulawesi - Eva Afriana Hamka (AMANAH: Jurnal Manajemen Keuangan Sektor Publik, 2026)
This study analyzes the relationship between regional financial policy and the process of structural economic transformation in South Sulawesi Province over the period 2019–2025. Using an applied macroeconomic approach based on a case study framework, the paper evaluates the effectiveness of regional budgets (APBD), sectoral spending patterns, and fiscal policy impacts on regional economic growth, poverty reduction, and income distribution. Key findings indicate that South Sulawesi recorded economic growth of 5.78% in the first quarter of 2025, surpassing the national average of 4.87%, while the poverty rate reached its lowest level in six years at 7.43% in September 2025. The 2026 regional budget was set at IDR 10.9 trillion with a locally generated revenue (PAD) target of IDR 5.76 trillion, reflecting fiscal intensification without rate increases. Despite these macro achievements, the study identifies three principal structural challenges: (1) a rising Gini coefficient of 0.363 indicating unequal distribution of growth benefits; (2) structural dependence on the primary sector contributing 24.7% of GRDP and vulnerable to external shocks; and (3) high fiscal dependency on central government transfers comprising approximately 50% of total regional revenue. Policy implications emphasize the need for economic base diversification, strengthening fiscal self-capacity, and accelerating downstream processing in agriculture and renewable energy as foundations for long-term structural transformation.